2021
DOI: 10.1002/evl3.242
|View full text |Cite
|
Sign up to set email alerts
|

A century-long record of plant evolution reconstructed from a coastal marsh seed bank

Abstract: Evidence is mounting that climate‐driven shifts in environmental conditions can elicit organismal evolution, yet there are sparingly few long‐term records that document the tempo and progression of responses, particularly for plants capable of transforming ecosystems. In this study, we “resurrected” cohorts of a foundational coastal marsh sedge (Schoenoplectus americanus) from a time‐stratified seed bank to reconstruct a century‐long record of heritable variation in response to salinity exposure. Common‐garden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 69 publications
3
25
0
Order By: Relevance
“…Our findings build on prior work (Blum et al, 2021;Jarrell et al, 2016;Saunders, 2003;Summers et al, 2018), indicating that S. americanus can serve as a model for studying persistent soil-stored seed banks and for using dormant propagules to infer evolutionary change of an ecosystem engineer over ecologically-relevant timescales. Evidence that in situ viability of S. americanus seeds extends for a century or more helps lay the foundation for further inquiry about the ecophysiology, environmental conditions, and evolutionary drivers of aging, decay, and dormancy of soil-stored seeds (Long et al, 2015).…”
Section: Con Clus Ionssupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings build on prior work (Blum et al, 2021;Jarrell et al, 2016;Saunders, 2003;Summers et al, 2018), indicating that S. americanus can serve as a model for studying persistent soil-stored seed banks and for using dormant propagules to infer evolutionary change of an ecosystem engineer over ecologically-relevant timescales. Evidence that in situ viability of S. americanus seeds extends for a century or more helps lay the foundation for further inquiry about the ecophysiology, environmental conditions, and evolutionary drivers of aging, decay, and dormancy of soil-stored seeds (Long et al, 2015).…”
Section: Con Clus Ionssupporting
confidence: 79%
“…Our work also offers some guidance for breaking dormancy to assemble depth/age cohorts of S. americanus for time-shift experiments (Blanquart & Gandon, 2013) to explore the role of adaptation in response to past and near-term future environmental change (Bustos-Segura et al, 2014;Davis et al, 2005;Orsini et al, 2013). With further refinement, the use of soil-stored seed banks could provide more realistic contexts, in contrast to space-for-time approaches (Shaw & Etterson, 2012), for inferring the progression of evolution in natural populations (Blum et al, 2021), and thus eventually emerge as a powerful complement to similarly-minded approaches that rely on ex situ seed archives (Etterson et al, 2016;Everingham et al, 2021;Franks et al, 2008;Summers et al, 2018;Weis, 2018).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…We conducted a common-garden experiment (Figure 1) using plants derived from seeds comprising an ancestral (c. 100 year-old seeds) and a descendant (c. 10 year-old) age cohort (Summers et al, 2018;Blum et al, 2021; SM and CI exhibit differences in soil biogeochemistry and plant community composition. For instance, SM soils are more organic and have less Fe (Weiss et al, 2004).…”
Section: Experimental Designmentioning
confidence: 99%
“…Our findings highlight the potential importance of ecological interactions and evolution in determining the fate of ecosystems experiencing pressures linked to climate change. Natural surveys (Blum et al, 2010) and experiments (Blum et al, 2021;Erickson et al, 2007;Gentile, 2015) have shown that salinity strongly influences the distribution, growth, and phenotype of S. americanus.…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 1 more Smart Citation